War experiences, economic grievances, and political participation in postwar societies: An empirical analysis of Kosovo. (July 2019) - Freitag, Markus; Kijewski, Sara; Oppold, Malvin
This article contributes to the debate evolving around the political legacy of armed conflict. We evaluate the effect of war experiences during the 1998–1999 civil war in Kosovo on various modes of political participation. We find that war victims are on average more likely to participate in non-institutionalized forms of participation such as signing petitions and to participate in protests in the postwar era. In addition, we show that the impact of war experiences on political protest is contingent upon the postwar situation. War experiences are linked to protest behavior when a survivor is economically disadvantaged after the war. However, war experiences lose their impact on protest behavior when people do not encounter economic grievances in the postwar environment. In this vein, exploring the postwar context enriches our understanding of the political legacy of war victimization.